The Autonomous Learnersâ Language Learning Strategies at Senior High Schools in Coastal Areas of Riau Province - Indonesia - Ras, Fakhri (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The aim of this study is to examine the relationship between language learning strategies used by autonomous learners of senior high schools in coastal areas based on type of school, and academic factors. In addition, this study is also to identify the strategies used by the respondents to learn English in general, four language skills, vocabulary, and structure. The population of the study are all autonomous learners from senior high schools in the coastal areas. As big as3000 students. The sample size is taken randomly as big as 10 % or 300 students out of the population. The Strategy Inventory for Language Learning (SILL) (Oxford; 1989) is used to get the quantitative data and interview is conducted to 60 selected students taken from the sample in order to have the qualitative data. Descriptive and inferential statistics are applied to analyze the data on the use of the language learning strategies (SILL). One-Way Anova is taken to determine the differences of language learning strategies usage based on academic, and type of school. The findings show different language learning strategies among the students based on type of school, and academic factors. The students used social strategy (mean: 4.02) as the most effective strategy. The implication of the study is that language learning strategies should be well informed and discussed throughly in the classroom.